PENERAPAN METODE PEMBELAJARAN TALKING STICK DALAM MENINGKATKAN MINAT BACA PADA MATA PELAJARAN BAHASA INDONESIA DI KELAS 3 SD - Aminatus Sa'diyah; Diana Ermawati; Imada Khairunisa (STKIP Subang, 2025)
The aims of the research is to describe the application of the Talking Stick learning method in increasing reading interest in Indonesian language subjects in grade 3 Elementary School of Demangan Kudus. The method used in this research is Classroom Action Research which is carried out in two cycles. This research was carried out from March-April 2025, at Elementary School of Demangan Kudus. This research contains the activities of classroom teachers in providing action to students, especially in Indonesian language learning using the Talking Stick method which requires students to be ready face future challenges by improving reading interest. The results of the study showed that the increase in reading interest in grade 3 Elementary School of Demangan Kudus starting from Pre-cycle was 50%, cycle I 58.4%, and cycle II 75.9%. This increase shows that the talking stick learning method can be used as a solution to increase reading interest in Indonesian language subjects.